Rapid Rescue Tie (2025)
Prehospital care plays a pivotal role as the initial step in managing various injuries. Nonetheless, a study involving interviews with healthcare professionals has shed light on several needs within this realm. These needs include an insufficient supply of equipment for hemorrhage treatment, inadequate training for paramedical personnel to efficiently implement protocols, and shortcomings in hemorrhage control during patient transport. To address these concerns, an investigation is conducted encompassing aspects such as incidence, pathophysiology, existing solutions, stakeholders, and market analysis for each identified need. This comprehensive approach guides the selection of the need, which is the control of hemorrhage.